2-mercaptoethane sulfonate (MESNA) protects against biliary obstruction-induced oxidative damage in rats - ERCAN, FERİHA; ŞENER, GÖKSEL; KABASAKAL, LEVENT (ELSEVIER IRELAND LTD, 2006)
The aim of this study was to assess the antioxidant and antifibrotic effects of chronic administration of 2-mercaptoethane sulfonate (MESNA) on oxidative liver damage and fibrosis induced by biliary obstruction in rats. Liver fibrosis was induced in male Wistar albino rats by bile duct ligation and scission (BDL). MESNA (150 mg/kg, i.p.) or saline was administered for 28 days. At the end of the experiment, rats were killed by decapitation. Serum aspartate aminotransferase (AST), and alanine aminotransferase (ALT) levels were determined to assess liver function. Tumor necrosis factor-alpha (TNF-alpha) and lactate dehidrogenase (LDH) were also assayed in serum samples. Liver tissues were taken for determination of the free radicals, hepatic malondialdehyde (MDA) levels, an end product of lipid peroxidation; glutathione (GSH) levels, a key antioxidant; myeloperoxidase (MPO) activity, as an indirect index of neutrophil infiltration. Hepatic collagen content, as a fibrosis marker was also determined. Serum AST, ALT, LDH and TNF-alpha levels were elevated in the BDL group as compared to control group, while this increase was significantly decreased by MESNA treatment. BDL caused a significant (p < 0.05-0.001) decrease in GSH levels while MDA levels and MPO activity were increased in the liver tissue. These changes were reversed by MESNA treatment. Collagen contents of the liver tissue was increased by BDL (P < 0.001), and reversed back to the control levels with MESNA. Since MESNA administration alleviated the BDL-induced oxidative injury of the liver and improved the hepatic functions, it seems likely that MESNA with its antioxidant and antifibrotic properties, may be of potential therapeutic value in protecting the liver fibrosis and oxidative injury due to biliary obstruction. (c) 2006 Published by Elsevier Ireland Ltd.
Keywords: MESNA; bile duct ligation; oxidative damage; fibrosis; BILE-DUCT LIGATION; MYELOPEROXIDASE ACTIVITY; ISCHEMIA-REPERFUSION; LIPID-PEROXIDATION; N-ACETYLCYSTEINE; REACTIVE OXYGEN; HEPATIC-INJURY; LIVER FIBROSIS; RENAL-FAILURE; FREE-RADICALS